Learning english language with technology : case study of a primary school in Kota Belud, Sabah - Tan, Choon Keong; Lee, Kean Wah (Penerbit Universiti Malaysia Sabah, 2016)
Teaching English language in primary school using ICT technology is a great challenge for language teachers. The study investigates how 40 voluntary student teachers of a public university in Sabah use ICT and multisensory approach to teach English. The study employs The Learner Centric Ecology of Resources Framework (Luckin, 2008) as a guide to observe knowledge scaffolding of students learning. Focus group interviews to elicite qualitative data were done with some selected student teachers who participated in the voluntary teaching job at selected primary school in Kota Belud, Sabah. The results showed that the majority of the student teachers were motivated to teach English using multisensory approach because it helped them to connect English with outside world via visual aids (multimedia). The student teachers’ reflective journals also indicated that they were able to align the ICT materials with the proficiency level of the students, create interactive teaching and learning materials, using ICT to improve class control because the graphics and sounds attracted students’ attention. All the actions by the student teachers proved that they were frequently updating each other in teaching like how the Luckin’s framework suggested. If this method of learning is practiced by more schools, it would make language learning interesting.